2009
DOI: 10.1007/978-3-642-02771-0_41
|View full text |Cite
|
Sign up to set email alerts
|

A High-Level Haptic Interface for Enhanced Interaction within VirtoolsTM

Abstract: Abstract.Haptics is the outstanding technology to provide tri-dimensional interaction within Virtual Environments (VE). Nevertheless, many software solutions are not fully prepared to support Haptics. This paper presents a user-friendly implementation of Sensable Phantom haptic interfaces onto the interactive VE authoring platform, Virtools 4.0. Haptics implementation was realized using the Haptic Library (HLAPI) from OpenHaptics toolkit 2.0 which provides highly satisfactory custom forces effects. The integra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…They implemented direct object manipulation simulation which allowed the user to grasp and release virtual objects in a natural way. Poyade et al [10] implemented a friendly enduser Sensable Technologies PHANToM haptic interface and its usability was studied through a reassembly task in crusher maintenance. They concluded that haptic devices are a powerful interaction tool in virtual maintenance tasks even when participants felt that the haptic force feedback was far from realistic force models.…”
Section: Related Workmentioning
confidence: 99%
“…They implemented direct object manipulation simulation which allowed the user to grasp and release virtual objects in a natural way. Poyade et al [10] implemented a friendly enduser Sensable Technologies PHANToM haptic interface and its usability was studied through a reassembly task in crusher maintenance. They concluded that haptic devices are a powerful interaction tool in virtual maintenance tasks even when participants felt that the haptic force feedback was far from realistic force models.…”
Section: Related Workmentioning
confidence: 99%
“…The haptic interface (driver) is introduced in more details in [14]. The driver also takes care of hapticalization of virtual models.…”
Section: Fig 1 Haptic User Interface Of Maintenance Planning Integrmentioning
confidence: 99%